Systematic Review of Gender and Humanitarian Situations Across Africa. Issue 3 (December 2022) - Nwoke, Chikezirim; Cochrane, Logan
For decades, as evidenced in programming and research, the humanitarian community has recognised gender equality and equity as integral to effective programming and response. Drawing upon ninety-nine publications indexed on the Web of Science and Google Scholar, this paper explores available evidence on gender and crisis settings in Africa to synthesise and critically analyse what is being learned. We found that limited research and programming have explicitly aimed to have gender transformative impacts, and those that do fail to adequately declare or reflect on the biases and intricacies of aiming to transform social norms in complex sociocultural contexts. Additionally, this review examines the trend of the body of research, highlighting the affiliation of authors and the geographical areas of focus. Evidence shows that research in this area is dominated by scholars affiliated with institutions in the Global North, raising questions relating to knowledge production and epistemic injustice in Africa.